1993
DOI: 10.1037/1040-3590.5.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Representation of personality disorders in circumplex and five-factor space: Explorations with a clinical sample.

Abstract: This study examined the relationship between DSM-IH-R personality disorders and the interpersonal circumplex and Big Five models of personality traits. One hundred and two consecutive referrals for group therapy for personality disorders were evaluated using the Personality Disorder Examination (PDE) and the Millon Clinical Multiaxial Inventory II (MCMI-II) personality-disorder scales. Their placement in circumplex space was assessed using the Inventory of Interpersonal Problems Circumplex Scales, whereas thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
186
2
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(224 citation statements)
references
References 33 publications
33
186
2
3
Order By: Relevance
“…concluded that "parallelism between the circumplex and hierarchical factor models reflects the parallelism between the radex and hierarchical factor models...on abilities." However, Soldz et al (1993) found that while many personality disorders could be located within the circumplex model, their placement within the hierarchical factor model provided a more accurate representation. In Zuckerman's (1991, p. xi) view, "the hierarchical model of traits...is best because it can encompass both broad and narrow traits.…”
Section: Factor Analysis Of Intellectual Abilitiesmentioning
confidence: 95%
See 2 more Smart Citations
“…concluded that "parallelism between the circumplex and hierarchical factor models reflects the parallelism between the radex and hierarchical factor models...on abilities." However, Soldz et al (1993) found that while many personality disorders could be located within the circumplex model, their placement within the hierarchical factor model provided a more accurate representation. In Zuckerman's (1991, p. xi) view, "the hierarchical model of traits...is best because it can encompass both broad and narrow traits.…”
Section: Factor Analysis Of Intellectual Abilitiesmentioning
confidence: 95%
“…Brody (1992), and Marshalek, Lohman, and Snow (1983) showed that the factor analytically derived hierarchical model is compatible with Guttman's radex theory. Soldz, Budman, Demby, and Merry (1993) reported that whereas personality disorders can be meaningfully located in circumplex space, application of a hierarchical model enables more appropriate location of several disorders. Cattell (1983) and Eysenck (1991Eysenck ( , 1992 have argued strongly for the importance of hierarchical models (see also the chapter by Stankov, Boyle, & Cattell).…”
Section: Factor Analysis Of Intellectual Abilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The alpha coefficients in this sample ranged from .76 for the Intrusive scale to .88 for the Nonassertive scale. The validity of the IIP-C has been supported in investigations of its relations with various forms of psychopathology (e.g., Kachin et al, 2001;Soldz, Budman, Demby, & Merry, 1993), therapeutic alliance (e.g., Muran et al, 1994), and psychotherapy outcome (e.g., Grosse Holtforth, Lutz, & Grawe, 2006;Maling et al, 1995;Ruiz et al, 2004).…”
Section: Interpersonal Measuresmentioning
confidence: 99%
“…From this perspective, PDs can be considered as an extreme trait level of a normal personality dimension, or as dysfunction associated with general personality traits. 3 Several studies have tried to capture PDs using a large variety of instruments in normal and clinical samples [4][5][6][7] ; however, at the moment there is still no consensus on one particular dimensional model to assess PDs. However, Clark 1 suggested the use of the FFM or some variant of the FFM because it has acquired the status of a reference model for the description of normal personality traits and is widely accepted.…”
mentioning
confidence: 99%